Three-dimensional analytical model for the pull-out response of anchor-mortar-concrete anchorage system based on interfacial bond failure. (1st February 2019) - Wang, Yan-Jie; Wu, Zhi-Min; Zheng, Jian-Jun; Zhou, Xiang-Ming
Highlights: Three-dimensional analytical model is proposed for the pullout response of anchors. The ultimate load and load-displacement response have been predicted and verified. The bond length determines the possible stages in the evolution of debonding. The bond length plays a pivotal role in the load-displacement response of anchors. Abstract: The interfacial bond behavior plays a significant role in determining the load transfer performance of anchor systems. Numerous analytical models have been proposed to investigate the pull-out behavior of grouted anchors, but no closed-form three-dimensional solution has been derived for the pull-out response of anchor systems with respect to interfacial bond failure. By considering the bond failure at the anchor-mortar interface, this paper presents a three-dimensional analytical model for predicting the pull-out response of grouted anchors based on a tri-linear bond-slip model. Specifically, the closed-form expressions are derived for the axial displacement, axial stress, and shear stress of the anchor and concrete, the load-displacement relationship of the anchor, and the interfacial shear stress at various possible pull-out stages. Furthermore, the load-displacement relationships and interfacial shear stress distributions are analyzed for different bond lengths during the whole pull-out process. The validity of the three-dimensional model is verified with experimental results collected from the literature. Through a systematic parametric study, the effect of bond length on the ultimate load and load-displacement response is investigated with the proposed model. It is shown that the ultimate load increases with the increase of bond length significantly before a critical bond length is reached but thereafter at a smaller and steady rate. Moreover, a longer bond length improves the ductility of the anchorage and the snapback phenomenon in the load-displacement response is dependent on the bond length, while the intensity of snapback increases with an increase in bond length. The proposed model is capable of better understanding the debonding mechanism and can be employed by engineers and researchers to predict the ultimate load capacity and load-displacement response of anchor systems.